Chemopreventive Measurements and Oxidative Stress Effects of Terpenoid-rich Canarium odontophyllum Miq. Leaf Extract (TRCO) in Ultraviolet B-Induced In-Vitro Skin Carcinogenesis Model - Abdul Aziz, Muhammad Wahizul Haswan; Basri, Dayang Fredalina; Masre, Siti Fathiah; Ghazali, Ahmad Rohi (Oriental Scientific Publishing Company, 2023)
The most common type of cancer found in the human outer and middle skin layers is keratinocyte carcinoma, often known as non-melanoma skin cancer. Although it can be aggressive, skin cancer is generally not fatal. This study aims to measure the chemopreventive and oxidative stress effects of terpenoid-rich Canarium odontophyllum Miq.’s leaf extract (TRCO) in the UVB-induced skin carcinogenesis model. The model involving human keratinocytes (HaCaT) was adapted with optimisations with pretreatment of 500 μg/ml TRCO (TRCO500) & 1000 μg/ml TRCO (TRCO1000). The HaCaT oncogenic transformation model’s repetitive UVB exposure resulted in altered cell shape, according to our findings. Pretreatment of TRCO1000 significantly reduced tumour protein p53 (TP53) and marker of proliferation KI-67 (KI67) expression in UVB-induced HaCaT. Treatment with TRCO resulted in an overall reduction in oxidative stress. TRCO pretreatment showed reduced lipid peroxides, LPO and significantly reduced protein carbonyls. In conclusion, the promising results of this chemopreventive study using TRCO on this in-vitro skin carcinogenesis model suggested that it is worthwhile to conduct further isolations and assessments of terpenoids from C. odontophyllum Miq. leaf as a possible chemoprevention agent.